MODEL HETEROGEN PENGERINGAN BUTIRAN JAGUNG DALAM UNGGUN DIAM - Istadi Istadi; J. P Sitompul (Mesin, 2000)
This paper deals with one-dimensional dynamic modelling and simulation of deep -bed com drying by two-phase model or heterogeneous model The models consider mass and heat transfer process within grain and drying air phase. This model also considers moisture content and temperature gradient within grain. The coupled of partial differential equations developed, then solves numerically by ï¬nite difference with altemating direction implicit method algorithm. The dynamic models predict not only humidity and temperature of outlet drying air, but also grain moisture content and temperature. The simulated proï¬les are compared with expenmental data, taken from available literature. The models can describe corn grain drying process in deep -bed dryer. However, the model parameters should be modiï¬ed to get drying characteristic proï¬les that closed to the experimenal data.